Application of Responsibility Accounting to Productivity Evaluation in the Nigerian Quoted Companies - Adegbie, Folajimi Festus; Rotimi, Olusanjo Olugbenga; Samuel, Olaoye A. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The study was designed to identify measure of performance that is related to shareholders wealth and that managers can directly observe and can see the influence of their actions in their responsibilities. The primary objective of business is to maximize the shareholders wealth. The measurement of firm’ s productivity is a good indicator to assess the realization of this objective. The responsibility to achieve this goal however lies heavily in the hands of managers which has become a major challenge in profit oriented organizations. It has been observed that responsibility accounting application to evaluate productivity is missing in Nigerian quoted companies, while in some it is not well instituted and administered. The research work adopted an ex-post facto research design, with a focus on the quoted Nigerian quoted companies as at 31st December 2016.A sample size of 53 companies was selected by using a combination of stratified and purposive sampling techniques. Productivity was proxied by earnings per share while Responsibility accounting was proxied by cost of sales, operating cost, net income and Return on Asset. Descriptive and inferential statistics were used for data analyses. The data collected were analyzed using specified regression models with the aid of E-View statistical package. The findings showed that responsibility accounting variables of cost of sales, operating cost, net income and return on assets have positive and significant impact on earnings per share with p values of t statistics < 0.05.The joint effect of cost of sales, operating cost, net income and return on asset on earning per share is significant. The F-statistics and Adjusted R2 values were prob.F=0.000,R2=0.37.The Adjusted R2 value was not strong in explaining the variations in earning per share. This implied that cost of sales, operating coat, net income and return on asset do not sufficiently explained variations in earning per share. We concluded that responsibility accounting has a significant positive effect on productivity in Nigerian quoted companies. This showed that if all the independent variables can be efficiently managed and controlled, value will be created in the quoted companies. We recommended that managers in profit centres, cost centres and investment centres should focus their actions towards the company’s productivity and maximization of the company’s value and shareholders wealth.